Kelimpahan dan Keanekaragaman Plankton Sebagai Bioindikator Kualitas Air di Perairan Pantai Sayung Kabupaten Demak Jawa Tengah - Maya Evita, Isnaini Nurul; Hariyati, Riche; Hidayat, Jafron Wasiq (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Sayung coast is a area with a growing residential, sea ranching, and industrial area. Those aspects produce create waste that could harm the environment, directly or indirectly. Plankton is a biologic component that is used to indicate the changes of water quality in waters that has been polluted. These goals of this research are to know the water quality in Sayung coast area from the abundance of the plankton, physical-chemical parameter of the water, and also the status of water saprobity. The samples are taken in July 2017 and April 2018, in Sayung coast waters, Demak. Plankton sampling and water from 5 sampling stasions are considered to represent the diversity of the plankton and water stability. Plankton is sampled using plankton net No.25, then preserved using 70% alcohol + 4% formaldehyde. The abiotic data measureted is nitrate content, temperature, pH, salinity, DO, and turbidity. Data analysis are done using Shannon Weiner’s diversity index (H’), diversty index (e), domination index (C), saprobic index. The result shows that there are 49 species of planktons are found, which are 38 fitoplankton, and 11 zooplankton. The highest group is Bacillariophyta which is 14,24%. The diversty index value of H’ 1,58 – 2,45; therefore the Sayung coast waters is catagorized as stable. The index value of e ranges from 0,64 – 1; index C values ranges from 0,08 – 0,22; and the saprobirity index value is in β-Meso/Polisaprobik to α-Mesosaprobik phase with a very light to very high pollution levels. The physical-chemical parameter analysis of Sayung coast waters in overall is still suitable to support plankton’s life.